The Relationship Between Sitting Duration And Flexibility Hamstring Muscle In Employees At RSUD Ngimbang - Wibowo, Hardianto; Rahmanto, Safun; Lubis, Zidni (Fakultas Keperawatan dan Fisioterapi Institut Kesehatan Medistra Lubuk Pakam, 2023)
Some employees at Ngimbang Hospital work activities are carried out in a sitting position for a long duration and almost done every day, especially for office administration employees. This will pose a risk of musculoskeletal disorders, especially hamstring muscle flexibility. A decrease in muscle flexibility will affect body fitness which can affect the work productivity of these employees. This study aims to determine the relationship between sitting duration and hamstring muscle flexibility. This study used a Cross Sectional Study research design involving 32 employee samples. Sitting duration is the independent variable while the dependent variable is hamstring muscle flexibility. The results of the normality test using the Shapiro-wilk test showed that the sitting duration variable was worth 0.000 and the hamstring muscle flexibility variable was worth 0.799, meaning that there was one variable that was not normally distributed, while the correlation test using Spearman obtained a value of 0.000 (<0.05). It is concluded that there is a relationship between sitting duration and hamstring muscle flexibility in employees at Ngimbang Hospital. The longer the duration of sitting, the more hamstring muscle flexibility decreases.